PSYCHOLOGİCAL FEATURES OF SELF-REGULATİON MECHANİSMS İN STRESSFUL SİTUATİONS - Eyazzade, Aynur (Health and Society, 2024)
The article is devoted to the study of the psychological characteristics of self-regulation mechanisms in students in stressful situations. In the article, the theoretical analysis and generalization of works related to the problem, a set of psychodiagnostic methods were used. The research base was the requirements of Odlar Yurdu University and various faculties of Baku State University. 135 second and third year students aged 18-23 participated in the study. A systematic approach was applied to the description and study of the research object for the reliability and validity of the research results. Mathematical methods were used for empirical data processing. Thus, according to the results of the correlation analysis, a relationship between stress resistance and self-regulation was found among the respondents. We see a negative relationship (r≤0.01) between stress resistance and self-regulation and one of its styles. This shows that there is a correlation between stress resistance, self-esteem and emotional stability and self-regulation. As self-regulation increases, the impact of stressful situations decreases. We believe that the present analysis can contribute to a better understanding of the mechanisms underlying successful and unsuccessful stress regulation. It should be taken into account that this will help prevent mental disorders and improve treatment.